Influence of graphene oxide on the mechanical, thermal and roughness of polyethersulphone - Sabet, M. (Springer, 2022)
Polyethersulphone (PES) is a prominent engineering plastic and its characteristics must be increased because of its promise functions in the aviation, vehicle industries and even sports fields. In this study, PES, and PES/graphene oxide (GO) composites are organized using extrusion blending methods. In this study, GO loading is suggested to increase PES compositesâ mechanical characteristics, dimensional strength and cryogenic engineering applications. The dynamic mechanical analysis displays that the loss and storage modulus of composites successfully increase with the GO inclusion, suggesting that the GO loading causes a powerful interfacial contact among the PES structure. The optimum GO loading for developing overall composite mechanical efficiency is 0.5 wt. It has been shown that GO inclusion improves the cryogenic mechanical characteristics. Besides, the cryogenic mechanical characteristics of PES and its composites at â70Â°C have been seen to be much superior to those at room temperature. The impact of GO loadings on the morphology and efficiency of the composites was studied by scanning electron microscopy, X-ray diffraction, Fourier-transform infrared spectroscopy and atomic force microscopy. Â© 2022, Indian Academy of Sciences.